A 20-year multicentre outcome analysis of salvage mechanical circulatory support for refractory cardiogenic shock after cardiac surgery. Issue 1 (December 2016) - Khorsandi, Maziar; Dougherty, Scott; Sinclair, Andrew; Buchan, Keith; MacLennan, Fiona; Bouamra, Omar; Curry, Philip; Zamvar, Vipin; Berg, Geoffrey; Al-Attar, Nawwar
Abstract Background Refractory post-cardiotomy cardiogenic shock (PCCS) is a relatively rare phenomenon that can lead to rapid multi-organ dysfunction syndrome and is almost invariably fatal without advanced mechanical circulatory support (AMCS), namely extra-corporeal membrane oxygenation (ECMO) or ventricular assist devices (VAD). In this multicentre observational study we retrospectively analyzed the outcomes of salvage venoarterial ECMO (VA ECMO) and VAD for refractory PCCS in the 3 adult cardiothoracic surgery centres in Scotland over a 20-year period. Methods The data was obtained through the Edinburgh, Glasgow and Aberdeen cardiac surgery databases. Our inclusion criteria included any adult patient from April 1995 to April 2015 who had received salvage VA ECMO or VAD for PCCS refractory to intra-aortic balloon pump (IABP) and maximal inotropic support following adult cardiac surgery. Results A total of 27 patients met the inclusion criteria. Age range was 34–83 years (median 51 years). There was a large male predominance (n  = 23, 85 %). Overall 23 patients (85 %) received VA ECMO of which 14 (61 %) had central ECMO and 9 (39 %) had peripheral ECMO. Four patients (15 %) were treated with short-term VAD (BiVAD = 1, RVAD = 1 and LVAD = 2). The most common procedure-related complication was major haemorrhage (n  = 10). Renal failure requiring renal replacement therapy (n  = 7), fatal stroke (n  = 5), septic shock (n  = 2), and a pseudo-aneurysm at the femoral artery cannulation site (n  = 1) were also observed. Overall survival to hospital discharge was 40.7 %. All survivors were NYHA class I-II at 12 months' follow-up. Conclusion AMCS for refractory PCCS carries a survival benefit and achieves acceptable functional recovery despite a significant complication rate.